AGING, BODY PRACTICES, GENDERED SUBJECTIVITY AND LATER LIFE IDENTITIES: NARRATIVES FROM INDIA AND CANADA. (11th November 2018) - Devi, A; Samanta, T
Abstract: The consumerist movement around medicalization of bodies and anti-aging technologies is re-defining how one grows old in today's societies. With the popularity of the "successful" and "active" aging paradigms, the socio-political expectations around growing old in industrialized societies, have shifted from the natural process of decline to a more preventive, medically focused process enhancing physical and cognitive plasticity. Parallel to this narrative of overzealous popular culture of fit, healthy and successful aging, growing old in India is often characterized by dependence, illness, withdrawal from the material world and gradual recourse to religion and spirituality. This study offers a critique of the "successful'' and "positive" aging paradigms, and asserts that these parallels have gendered implications on identity, self-representation and citizenship of aging women (and men) in both the societies. Based on qualitative interviews of 45 older adults (aged above 54 years) of Indian origin, this study engages in a cross-national comparison of narrative accounts of everyday body practices, perceptions and lived experiences of growing old in two urban settings in India (Ahmedabad) and Canada (Vancouver). In the process, this study also analyzes the influence of migration and acculturation on aging bodies, and examines how the older adults, particularly older females, navigate the socio-cultural shift in their efforts to maintain personal continuity, identity and selfhood through everyday practices. Further, drawing from cultural gerontological understanding, this study reflects on how the neoliberal movements of consumerism, healthism and body/beauty practices are changing older adult's negotiations with intimate relationships, family, peer networks, religion, and death.